BODY COMPOSITION AND ITS RELATIONSHIP TO SPORTS INJURIES IN YOUNG FEMALE ACROBATIC GYMNASTS - Yaiza Taboada-Iglesias; Diego Alonso-Fernández; Xoana Reguera-; Águeda Gutiérrez-Sánchez (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
The risk of injury is associated with elite sport. There is evidence that body composition may affect injury risk. The aim of this study was to analyze the incidence of injuries, and to determine the relationship of body composition with the incidence, typology and severity of injuries in female acrobatic gymnasts. The sample included 92 female acrobatic gymnasts aged between 9 and 20 years (13.66 ± 2.66 years), 33 tops (11.06 and 1.41 age) and 59 bases (15.11 and 2.00 age). Body measurements (fat percentage, muscle percentage and the sum of 6 skinfolds), and body mass index (BMI) and their categorization into underweight, normal weight and overweight, were measured. Data about injuries were collected through a self-completed questionnaire at the end of the season, where it was recorded whether they had suffered injuries, the type of injury (joint, ligament, tendon or bone) and its severity (minor, moderate or severe). A descriptive, comparative and relational analysis of the studied variables and between groups was carried out. The results obtained in this study indicate a higher percentage of uninjured gymnasts, but also a high percentage of injured gymnasts, with ligament injuries being the most frequent. As for the relationship with body composition and BMI, no significant relationships were observed in the incidence, typology or severity of injuries suffered by these athletes. It only seems to affect tendon injuries in the bases, with the injured gymnasts having a higher BMI, fat percentage and the sum of six skinfolds.